Creative approach to shaping the symbolic system of global culture - Ten, Yulia Pavlovna (Creativity Studies, 2022)
The key idea of the paper consists in suggestion that globalization focuses on the integration of different cultures under the umbrella of common ideas, norms and values. The globalization’s challenge is the necessity of searching the ways and methods of overcoming the intercultural barriers among different peoples. The purpose of the research is to analyze the issue of creating a symbolic system global culture, the access to cultural code of this system will help the participants of intercultural communication to minimize the barriers that prevent the mutual understanding. The author guesses that symbols can be seen as the creative technology for shaping universal layer of a global culture. To access this “layer” of a global culture, communication subjects must have a common cultural code. The creative information and communication technologies help subjects of intercultural communication to be able to reveal the cultural codes of other cultural systems. The author puts forward the idea of the need for shaping of the universal “cultural knowledge network” on creative digital platform. The knowledge of the symbol system of a global culture can help all peoples to open new perspective of transcultural communication in the context of creating common non-verbal language for mutual understanding.